VPSA oxygen production molecular sieve and preparation method thereof
Through the preparation method of VPSA oxygen-making molecular sieve without binder, the sodium-based or sodium-potassium-based X-type molecular sieve raw powder and countercurrent circulating crystallization process was used to solve the problem of slow increase in the adsorption capacity of Li-LSX molecular sieve N2, and the preparation of molecular sieve with high nitrogen adsorption amount and nitrogen-oxygen separation coefficient was achieved.
Patent Information
- Application Number
- CN202411712862.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-04-15
AI Technical Summary
The existing Li-LSX molecular sieve has slowly increased N2 adsorption capacity under high lithium ion content, and the lithium resources are gradually decreasing, resulting in a sharp increase in lithium prices in the future, and it is necessary to develop alternative molecular sieves.
Using the preparation method of VPSA oxygen-making molecular sieve without binder, molecular sieve with high nitrogen adsorption and high nitrogen-oxygen separation coefficient were prepared by selecting sodium-based or sodium-potassium-based X-type molecular sieve raw powder, countercurrent cyclic crystallization process and calcium ion exchange.
High nitrogen adsorption amount, excellent nitrogen adsorption rate and high nitrogen-oxygen separation coefficient are achieved, and no binder is included, which improves the effective utilization rate of molecular sieves.
Smart Images

Figure BDA0005156190700000101 
Figure BDA0005156190700000111
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of molecular sieves, and in particular to a VPSA oxygen-generating molecular sieve and a preparation method thereof. Background Art
[0002] Oxygen is an important industrial raw material. Pressure swing adsorption (VPSA / PSA) oxygen production has the advantages of simple equipment, low investment, simple process, stability, reliability, rapid oxygen production, small footprint, few equipment, and high degree of automation. It is widely used in medical oxygen, small household oxygen, oxygen-enriched combustion, metal smelting and other fields. The core technology of pressure swing adsorption oxygen production is adsorbent. Oxygen molecular sieve adsorbent plays the role of enriching oxygen by its selective adsorption of nitrogen (N2).
[0003] Since lithium ions have the smallest radius, the largest charge-to-diameter ratio, and the highest charge density, they have a stronger effect on N2. Therefore, the main molecular sieve in the current PSA air separation oxygen production industry is LiLSX. However, studies have shown that: + When the molar percentage is greater than 70%, the N2 adsorption capacity will show a linear increase trend. With the rapid development of the lithium-ion battery (energy storage) industry, the consumption of lithium is gradually increasing, and the reserves of lithium are gradually decreasing, which makes the demand for lithium continue to grow. The price of lithium may rise sharply in the future. Therefore, the development of molecular sieves that can replace Li-LSX and can be used for air separation has become a trend in the development of oxygen molecular sieves.
[0004] Compared with lithium salts, calcium salts are not only cheap but also abundant in reserves. Calcium ions are divalent and have less shielding, so they can contact more adsorbate molecules. At the same time, they form strong electrostatic interactions with adsorbates (N2 and O2). Therefore, LSX zeolites containing calcium ions have been studied as potential alternatives in the past few decades. However, the effective utilization rate of the developed CaLSX shaped molecular sieves has been greatly reduced due to the presence of binders. Summary of the invention
[0005] In view of this, the object of the present invention is to provide a VPSA oxygen-generating molecular sieve and a preparation method thereof. The VPSA oxygen-generating molecular sieve prepared by the present invention does not contain a binder and has excellent nitrogen adsorption capacity and nitrogen adsorption rate.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing a VPSA oxygen-generating molecular sieve, comprising the following steps:
[0008] The X-type molecular sieve raw powder, a binder, an organic pore-forming agent and a molding liquid are mixed and molded to obtain a molecular sieve intermediate; the X-type molecular sieve raw powder is a sodium-based or sodium-potassium-based X-type molecular sieve raw powder, D50 The particle size is 0.1-1.0 μm, the silicon-aluminum ratio is 1.9-2.3, and the silicon-aluminum ratio is calculated as the molar ratio of SiO2 to Al2O3; the binder includes kaolin and / or kaolin; the molding liquid is a silicon source solution;
[0009] The molecular sieve intermediate is subjected to a first drying and a first calcination in sequence to obtain a primary calcination intermediate;
[0010] The primary calcined intermediate is subjected to countercurrent circulation crystallization using a silicon-containing alkaline aqueous solution to obtain a fully crystalline intermediate; the countercurrent circulation crystallization comprises an aging stage and a crystallization stage in sequence;
[0011] exchanging calcium ions on the fully crystalline intermediate to obtain an exchange intermediate;
[0012] The exchange intermediate is sequentially subjected to a second drying and a second calcination to obtain the VPSA oxygen-producing molecular sieve.
[0013] Preferably, the silicon-aluminum ratio of the binder is 1.75 to 2.3, and the silicon-aluminum ratio is calculated as the molar ratio of SiO2 to Al2O3.
[0014] Preferably, the organic pore former comprises one or more of corn starch, wheat starch and bran.
[0015] Preferably, the masses of the binder and the organic pore former are 5-10% and 0.5%-4% of the total mass of the X-type molecular sieve raw powder and the binder, respectively. The masses of the binder and the X-type molecular sieve raw powder are calculated on a dry basis.
[0016] Preferably, the silicon source in the silicon source solution includes one or more of white carbon black, silica gel powder, sodium silicate and silica sol, and the content of the silicon source in the silicon source solution is 2.0 to 6.0 g / L, and the content of the silicon source is calculated as SiO2.
[0017] Preferably, the molding method is:
[0018] The mixture of X-type molecular sieve raw powder, binder and organic pore-forming agent is sequentially mixed with molding liquid, first molded, dried and crushed to obtain crushed powder; the operations of mixing with molding liquid, first molded, dried and crushed are repeated, and the number of repetitions is ≥1 times;
[0019] The crushed powder is mixed with a molding liquid for a second molding to obtain a molecular sieve intermediate.
[0020] Preferably, the silicon content in the silicon-containing alkaline aqueous solution is 5 to 19 g / L, where the silicon content is calculated as SiO2; -The content is 2.26-2.90 mol / L; the solid-liquid ratio of the primary calcined intermediate to the silicon-containing alkaline aqueous solution is 1 kg:2.2-3.0 L.
[0021] Preferably, the temperature of the aging stage is 50-70°C, the time is 1-4 hours, and the countercurrent circulation flow rate of the silicon-containing alkaline aqueous solution is 1-4 m / s. 3 / h; the temperature of the crystallization stage is 80-100°C, the time is 3.5-7h, and the countercurrent circulation flow rate of the silicon-containing alkaline aqueous solution is 1-4m 3 / h.
[0022] Preferably, the temperature of the first drying is 80-200°C, and the holding time is 0.5-4h; the temperature of the first roasting is 620-750°C, and the holding time is 0.5-4h; the temperature of the second drying is 50-120°C, and the holding time is 1-2h; the temperature of the second roasting is 350-425°C, and the holding time is 3-8h.
[0023] The present invention provides a VPSA oxygen-producing molecular sieve prepared by the preparation method described in the above technical scheme. The crystal structure of the VPSA oxygen-producing molecular sieve is an X-type molecular sieve, does not contain a binder, and has a silicon-aluminum ratio of 1.9 to 2.3, where the silicon-aluminum ratio is calculated as the molar ratio of SiO2 to Al2O3.
[0024] The present invention provides a method for preparing a VPSA oxygen-generating molecular sieve. Compared with the prior art, the VPSA oxygen-generating molecular sieve prepared by the present invention has a high nitrogen adsorption capacity (≥1.4 mol / g (25°C, 760 mmHg)), a high nitrogen-oxygen separation coefficient (≥4.2 (25°C, 760 mmHg)), an excellent nitrogen adsorption rate, and a low impurity crystal content (A-type impurity crystal content ≤1%), as follows:
[0025] (1) The high nitrogen adsorption capacity and nitrogen-oxygen separation coefficient of the VPSA oxygen-generating molecular sieve are derived from the selection of X-type molecular sieve raw powder and the countercurrent circulation crystallization process. Among them, the sodium-based or sodium-potassium-based X-type molecular sieve raw powder of a specific particle size is conducive to the diffusion of calcium ions into the crystal structure of the molecular sieve, thereby increasing the ion exchange rate of the molecular sieve, and will not cause insufficient compactness of the base material due to the small particle size, making it difficult to form; the selection of the silicon-aluminum ratio of the sodium-based or sodium-potassium-based X-type molecular sieve raw powder itself has a high nitrogen adsorption capacity and nitrogen-oxygen separation coefficient. Furthermore, the proportion of inert binders kaolin and / or argillaceous clay is relatively small, which is beneficial for reducing the content of type A impurities in the crystallization intermediate and for increasing the exchange degree. At the same time, the molding process can make the intermediate product have a higher crushing resistance, ensuring that the finished product will not pulverize when used. In addition, the countercurrent circulation crystallization process is conducive to converting most or even all of the metakaolin (kaolin and / or kaolinite obtained by roasting) into X-type molecular sieves, while ensuring the uniformity and consistency of the content of impurity crystals in the fully crystalline intermediates, and the nitrogen adsorption of type A impurity crystals is relatively low.
[0026] (2) The VPSA oxygen-generating molecular sieve has an excellent nitrogen adsorption rate, which is derived from the sodium-based or sodium-potassium-based X-type molecular sieve raw powder D 50 The selection of pore-forming agent and primary calcination process. Among them, sodium-based or sodium-potassium-based X-type molecular sieve raw powder D 50 The pore size is small, which is beneficial for the diffusion of adsorbates such as nitrogen between the surface and the interior of the crystal structure unit in the molecular sieve; in addition, the selected pore-forming agent can be fully removed after one calcination and will not remain inside the molecular sieve, thereby forming a uniform pore structure in the molecular sieve, which is beneficial for the diffusion of adsorbates such as nitrogen between the surface and the interior of the molecular sieve.
[0027] (3) The content of type A impurity crystals in the VPSA oxygen-generating molecular sieve is ≤1%, which is derived from the primary calcination process and the countercurrent circulation crystallization process. The binder added during the molding process will reduce the effective adsorption capacity of the adsorbent per unit mass. The present invention can transform the reaction-inert kaolin and / or kaolinite with a stable structure into amorphous reactive metakaolin after the primary calcination process. Further, by controlling the calcination process conditions, the inert kaolin and / or kaolinite in the primary calcination intermediate can be completely transformed into active metakaolin. In addition, the countercurrent circulation crystallization process can further transform the active metakaolin into an X-type molecular sieve, which is convenient for the subsequent exchange. The reasons are as follows: (I) the alkaline source in the silicon-containing alkaline aqueous solution provides an alkaline environment for the aging and crystallization step, and at the same time can make up for the deficiency that the active kaolin cannot be converted into a molecular sieve due to the absence of Na2O in the active kaolin. The silicon in the silicon-containing alkaline aqueous solution can make up for the defect that the active kaolin cannot be converted into an X-type molecular sieve due to the low silicon source content in the active kaolin, thereby reducing the content of impure crystals; (II) the aging step forms crystal nuclei in the active kaolin, and the crystallization step makes the crystal nuclei gradually grow into an X-type molecular sieve with a certain grain size and silicon-aluminum ratio characteristics; (III) the silicon-containing alkaline aqueous solution in the countercurrent circulation process can flow fully, which can ensure the uniformity of the silicon-containing alkaline aqueous solution, and can make the primary roasting intermediate fully and uniformly contact with the silicon-containing alkaline aqueous solution, thereby ensuring the uniformity and consistency of the impure crystal content of the crystallization intermediate. DETAILED DESCRIPTION
[0028] The present invention provides a method for preparing a VPSA oxygen-generating molecular sieve, comprising the following steps:
[0029] The X-type molecular sieve raw powder, a binder, an organic pore-forming agent and a molding liquid are mixed and molded to obtain a molecular sieve intermediate; the X-type molecular sieve raw powder is a sodium-based or sodium-potassium-based X-type molecular sieve raw powder, D 50 The particle size is 0.1-1.0 μm, the silicon-aluminum ratio is 1.9-2.3, and the silicon-aluminum ratio is calculated as the molar ratio of SiO2 to Al2O3; the binder includes kaolin and / or kaolin; the molding liquid is a silicon source solution;
[0030] The molecular sieve intermediate is subjected to a first drying and a first calcination in sequence to obtain a primary calcination intermediate;
[0031] The primary calcined intermediate is subjected to countercurrent circulation crystallization using a silicon-containing alkaline aqueous solution to obtain a fully crystalline intermediate; the countercurrent circulation crystallization comprises an aging stage and a crystallization stage in sequence;
[0032] exchanging calcium ions on the fully crystalline intermediate to obtain an exchange intermediate;
[0033] The exchange intermediate is sequentially subjected to a second drying and a second calcination to obtain the VPSA oxygen-producing molecular sieve.
[0034] In the present invention, unless otherwise specified, the raw materials involved are commercially available products well known in the art.
[0035] The present invention mixes X-type molecular sieve raw powder, a binder, an organic pore-forming agent and a molding liquid to form a molecular sieve intermediate. In the present invention, the X-type molecular sieve raw powder is a sodium-based or sodium-potassium-based X-type molecular sieve raw powder. 50 The particle size is 0.1-1.0 μm, preferably 0.2-0.6 μm, and the silicon-aluminum ratio is 1.9-2.3, preferably 1.95-2.1, where the silicon-aluminum ratio is the molar ratio of SiO2 to Al2O3. The present invention defines the D of the sodium-based or sodium-potassium-based X-type molecular sieve raw powder as follows: 50 The particle size is conducive to the diffusion of calcium ions into the crystal structure of the molecular sieve in the subsequent calcium ion exchange, which increases the ion exchange rate of the molecular sieve without causing the D 50 Too small, resulting in insufficient compactness of the base material and difficulty in molding; the present invention limits the silicon-aluminum ratio of the sodium-based or sodium-potassium-based X-type molecular sieve raw powder, which can make the molecular sieve product have a higher nitrogen adsorption capacity and nitrogen-oxygen separation coefficient. In the present invention, the binder includes kaolin and / or sheep licorice, and the silicon-aluminum ratio of the binder is preferably 1.75-2.3, more preferably 1.8-2.1, and the silicon-aluminum ratio is measured by the molar ratio of SiO2 to Al2O3. In the present invention, the organic pore-forming agent preferably includes one or more of corn starch, wheat starch and bran. In the present invention, the molding liquid is a silicon source solution (the solvent is water), and the silicon source in the silicon source solution preferably includes one or more of white carbon black, silica gel powder, sodium silicate and silica sol, more preferably silica sol; the content of the silicon source in the silicon source solution is preferably 2.0-6.0g / L, more preferably 3.2-4.0g / L, and the content of the silicon source is calculated in SiO2.
[0036] In the present invention, the masses of the binder and the organic pore former are preferably 5-10% and 0.5%-4% of the total mass of the X-type molecular sieve raw powder and the binder, respectively, and more preferably 7-9% and 1.5-2.5%, respectively. The mass of the binder and the mass of the X-type molecular sieve raw powder are calculated on a dry basis.
[0037] In the present invention, the molding method is preferably:
[0038] The mixture of X-type molecular sieve raw powder, binder and organic pore-forming agent is sequentially mixed with molding liquid, first molded, dried and crushed to obtain crushed powder; the operations of mixing with molding liquid, first molded, dried and crushed are repeated, and the number of repetitions is ≥1 times;
[0039] The crushed powder is mixed with a molding liquid for a second molding to obtain a molecular sieve intermediate.
[0040] In the present invention, the operations of mixing with molding liquid, first molding, drying and crushing are repeated, that is, the mixture of X-type molecular sieve raw powder, binder and organic pore-forming agent is sequentially mixed with molding liquid, first molding, dried and crushed to obtain a crushed powder; then the crushed powder is repeatedly mixed with molding liquid, first molding, dried and crushed to obtain the crushed powder. In the present invention, the first molding is preferably kneaded to form a strip-shaped matrix material, and the strip-shaped matrix material is preferably 1 / 16 strip (strip diameter 1.5-1.7mm) or 1 / 8 strip (strip diameter 3.0-3.3mm), and the water content of the strip-shaped matrix material obtained after each first molding is preferably 36-39wt%, and the amount of molding liquid used for each mixing with molding liquid is based on meeting the above-mentioned water content requirement of the strip-shaped matrix material. In the present invention, the drying is preferably oven drying. In the present invention, the water content of the powder obtained by each crushing is preferably ≤12wt%, and the particle size is preferably <0.075mm. In the present invention, the number of repetitions is preferably 1 to 4 times, that is, the mixing with the molding liquid, the first molding, drying and crushing operations are performed 2 to 5 times in total. The X-type molecular sieve raw powder has a small fineness, and the repeated molding, drying and crushing operations can improve the compactness of the matrix material, so that the molecular sieve intermediate after the final molding has a higher crushing resistance.
[0041] In the present invention, the second molding is preferably carried out in a ball-forming device, specifically, the crushing powder is added while the molding liquid is added in the ball-forming device, and the balls are rolled. In the present invention, the water content of the molecular sieve intermediate is preferably 36-42wt%, more preferably 37-40wt%, and the molding liquid used in the second molding is based on meeting the above-mentioned water content requirement of the molecular sieve intermediate; the particle size of the molecular sieve intermediate is preferably 1.0-2.0mm.
[0042] After obtaining the molecular sieve intermediate, the present invention sequentially performs the first drying and the first calcination on the molecular sieve intermediate to obtain a primary calcined intermediate. In the present invention, the temperature of the first drying is preferably 80-200°C, more preferably 100-150°C, and the holding time is preferably 0.5-4h, more preferably 1-2h; the temperature of the first calcination is preferably 620-750°C, more preferably 660-720°C, and the holding time is preferably 0.5-4h, more preferably 1.5-3h. The binder kaolin and / or kaolinite added during the molding process will reduce the effective adsorption capacity of the unit mass of the adsorbent, and the present invention can convert the inert kaolin and / or kaolinite in the primary calcined intermediate into active metakaolin through the first calcination; and the pore-forming agent can be fully removed in the first calcination and will not remain inside the molecular sieve, thereby forming a uniform pore structure in the molecular sieve, which is conducive to the diffusion of adsorbates such as nitrogen between the surface and the inside of the molecular sieve.
[0043] After obtaining the primary calcined intermediate, the present invention uses a silicon-containing alkaline aqueous solution to perform countercurrent circulation crystallization on the primary calcined intermediate to obtain a fully crystalline intermediate. In the present invention, the silicon content in the silicon-containing alkaline aqueous solution is preferably 5 to 19 g / L, more preferably 9 to 14 g / L, and the silicon content is calculated as SiO2; the silicon in the silicon-containing alkaline aqueous solution is preferably provided by one or more of white carbon black, silica gel powder, sodium silicate and silica sol, more preferably provided by silica sol. In the present invention, OH in the silicon-containing alkaline aqueous solution - The content of OH in the silicon-containing alkaline aqueous solution is preferably 2.26 to 2.90 mol / L, more preferably 2.3 to 2.75 mol / L. - Preferably, it is provided by one or more of KOH, NaOH and refined silicon-containing alkaline recycling liquid. In the present invention, the solid-liquid ratio of the primary roasting intermediate to the silicon-containing alkaline aqueous solution is preferably 1kg:2.2-3.0L, more preferably 1kg:2.2-2.5L.
[0044] In the present invention, the countercurrent circulation crystallization includes an aging stage and a crystallization stage in sequence, that is, countercurrent circulation step-by-step crystallization. In the present invention, the temperature of the aging stage is preferably 50 to 70°C, more preferably 55 to 65°C, the time is preferably 1 to 4 hours, more preferably 2 to 3 hours, and the countercurrent circulation flow rate of the silicon-containing alkaline aqueous solution is preferably 1 to 4 m / s. 3 / h, more preferably 2.0 to 3.5 m 3 / h. In the present invention, the temperature of the crystallization stage is preferably 80-100°C, more preferably 90-98°C, and further preferably 92-95°C. The time is preferably 3.5-7h, more preferably 4-6h, and further preferably 4-5h. The countercurrent circulation flow rate of the silicon-containing alkaline aqueous solution is preferably 1-4m 3 / h, more preferably 2.0 to 3.5 m 3 / h, more preferably 2.5 to 3m 3 / h.
[0045] In the present invention, the specific operation of the countercurrent circulation crystallization is preferably: the primary roasting intermediate is soaked in water and drained and then put into a crystallization column, the silicon-containing alkaline aqueous solution is transported to a circulation tank, and the circulation tank is heated; the silicon-containing alkaline aqueous solution is made to flow into the lower part of the crystallization column through a circulation pump, and flows out from the upper part, and flows back to the circulation tank, and countercurrent circulation crystallization is performed according to the above-mentioned process conditions for the aging stage and the crystallization stage. In the present invention, the heating method is preferably steam heating or electric heating, and the silicon-containing alkaline aqueous solution in the circulation tank is heated to meet the temperature requirements of the aging stage and the crystallization stage.
[0046] In the present invention, the aging stage can form a crystal nucleus in the active kaolin in the primary calcined intermediate, and the crystallization stage can gradually grow the crystal nucleus into a molecular sieve with a certain grain size and silicon-aluminum ratio. The alkali source in the silicon-containing alkaline aqueous solution provides an alkaline environment for the aging and crystallization steps, and can also make up for the deficiency that the active kaolin cannot be converted into a molecular sieve due to the lack of Na2O. The silicon in the silicon-containing alkaline aqueous solution can make up for the defect that the active kaolin cannot be converted into an X-type molecular sieve due to the low content of silicon source in the active kaolin, thereby reducing the content of impurity crystals. The present invention converts the binder into a molecular sieve through the countercurrent circulation crystallization, so the resulting molecular sieve product does not contain a binder.
[0047] After the countercurrent circulation crystallization, the obtained crystallization product is washed to obtain a fully crystalline intermediate (i.e., a sodium-based or sodium-potassium-based fully crystalline intermediate); the silicon-containing alkaline aqueous waste liquid after the countercurrent circulation crystallization is stored in a crude silicon-containing alkaline aqueous solution storage tank, and after filtering, a refined silicon-containing alkaline reuse liquid is obtained. In the present invention, the washing is preferably water washing until the pH value of the washing liquid is 10.5.
[0048] After obtaining the fully crystalline intermediate, the present invention performs calcium ion exchange on the fully crystalline intermediate to obtain an exchange intermediate. The present invention preferably uses a soluble calcium-containing inorganic salt aqueous solution to perform calcium ion exchange on the fully crystalline intermediate; the soluble calcium-containing inorganic salt in the soluble calcium-containing inorganic salt aqueous solution is preferably analytically pure calcium chloride and / or calcium nitrate, and the Ca in the soluble calcium-containing inorganic salt aqueous solution is preferably 1.5-2.0 wt.-1% 2.5-1 ... 2+ The content is preferably 0.5 to 2.5 mol / L, more preferably 1.0 to 2.3 mol / L, and further preferably 1.5 to 2 mol / L. In the present invention, the temperature of the calcium ion exchange is preferably 90 to 100°C, more preferably 94 to 98°C, and the temperature of the calcium ion exchange is preferably achieved by heating the soluble calcium-containing inorganic salt aqueous solution, and the heating method is preferably steam heating or electric heating.
[0049] In the present invention, the calcium ion exchange is preferably a countercurrent series exchange, and the specific operation of the countercurrent series exchange is preferably:
[0050] The fully crystalline intermediate is placed in an exchange column, and a soluble calcium-containing inorganic salt aqueous solution (exchange solution) is made to flow in from the lower part of the exchange column and out from the upper part through a delivery pump to perform a series exchange;
[0051] When the Ca of the molecular sieve on the first exchange column at the front end of the series system 2+ When the exchange degree is ≥96% (preferably ≥97%), the exchange intermediate is obtained by washing with deionized water at room temperature; after washing, the fully crystalline intermediate is refilled and connected in series to the end of the exchange system, and the exchange liquid enters from the lower part of the second adjacent exchange column, and the other exchange columns continue to exchange in series.
[0052] In the present invention, the number of exchange columns connected in series in the countercurrent series exchange is preferably ≥8, more preferably ≥10; during the countercurrent series exchange, the flow rate of the soluble calcium-containing inorganic salt aqueous solution is preferably 1.0 to 3.5 m / s. 3 / h, more preferably 2.0 to 2.5 m 3 / h.
[0053] After obtaining the exchange intermediate, the present invention sequentially performs a second drying and a second calcination on the exchange intermediate to obtain the VPSA oxygen-producing molecular sieve. In the present invention, the temperature of the second drying is preferably 50 to 120°C, more preferably 100 to 120°C, and the insulation time is preferably 1 to 2h, more preferably 1 to 1.5h; the temperature of the second calcination is preferably 350 to 425°C, more preferably 350 to 400°C, and the insulation time is preferably 3 to 8h, more preferably 5 to 6h, and the heating rate to the temperature of the second calcination is preferably 5 to 15°C / min. After the second calcination, the structural water inside the molecular sieve is removed, making the molecular sieve active, that is, the activated molecular sieve. After the second calcination, the obtained product is naturally cooled to room temperature in a dryer to obtain the VPSA oxygen-producing molecular sieve.
[0054] The present invention provides a VPSA oxygen-generating molecular sieve prepared by the preparation method described in the above technical solution. The VPSA oxygen-generating molecular sieve has an X-type crystal structure, does not contain a binder, and has a silicon-aluminum ratio of 1.9 to 2.3, preferably 2.0 to 2.1, and the silicon-aluminum ratio is calculated as the molar ratio of SiO2 to Al2O3. In the present invention, the static nitrogen adsorption capacity (25°C, 760mmHg) of the VPSA oxygen-generating molecular sieve is ≥1.45mmol / g, the nitrogen-oxygen separation coefficient (25°C, 760mmHg) is ≥4.2, and the content of type A impurities is ≤1% (type A impurities are characteristic peak).
[0055] In order to further illustrate the present invention, the VPSA oxygen-generating molecular sieve and the preparation method thereof provided by the present invention are described in detail below in conjunction with examples, but they should not be construed as limiting the scope of protection of the present invention.
[0056] Example 1
[0057] A VPSA oxygen-generating molecular sieve, the preparation steps are as follows:
[0058] (1) Take 40 kg of sodium-based X-type molecular sieve powder (silicon-aluminum ratio ((SiO2 / Al2O3) is 2.02), D 500.6μm, water content 20.2%), 3.5kg of binder sheep sweet soil (silicon aluminum ratio (SiO2 / Al2O3) is 1.95, water content 19.95%), 0.7kg of corn starch, the three raw materials and the molding liquid (the molding liquid used is a silica sol aqueous solution, wherein the SiO2 content is 3.6g / L) are mixed and kneaded to extrude into 1 / 8 of the matrix material (the water content of the matrix material is 38%), the matrix material is dried and crushed to obtain a primary crushed powder (the water content of the crushed powder is 8%, the particle size is ≤0 .065mm), knead the primary crushed powder and the molding liquid (the molding liquid used is a silica sol aqueous solution, wherein the SiO2 content is 3.6g / L) into 1 / 8 strips (the water content of the matrix material is 36.5%), dry and crush the matrix material again to obtain the secondary crushed powder (the water content of the crushed powder is 8%, and the particle size is ≤0.065mm); add the secondary crushed powder and the molding solution (silica sol aqueous solution, wherein the SiO2 content is 3.6g / L) into the ball forming equipment, roll into balls, and sieve out The intermediate product has a water content of 37wt%.
[0059] (2) 3.0 kg of the dry intermediate was dried at 150°C for 1 hour and then calcined in a muffle furnace at 720°C for 1.5 hours to obtain a primary calcined intermediate.
[0060] (3) After immersing 2.5 kg of the primary calcined intermediate in water and draining it, immerse it in a crystallization column containing 5.5 L of a silicon-containing alkaline aqueous solution (NaOH content of 2.7 mol / L, SiO2 content of 10.5 g / L), wherein the silicon-containing alkaline aqueous solution is heated in a circulation tank and flows into the crystallization column from the bottom through a circulation pump, flows out from the top, and then flows back to the circulation tank to form a series closed loop; first, at a flow rate of 3 m / s, the crystallization column is heated and then the crystallization column is cooled and cooled. 3 / h, countercurrent circulation crystallization at 62 ° C for 2 h, and then at a flow rate of 3m 3 / h, countercurrent circulation crystallization at 95°C for 5h, and washing with water until the pH value of the washing liquid is 10.5 to obtain a sodium-based fully crystalline intermediate.
[0061] (4) 1.2 kg of the sodium-based fully crystalline intermediate was evenly immersed in 12 exchange columns using Ca 2+ A 2 mol / L calcium ion aqueous solution (prepared from analytically pure calcium chloride) was stirred at a flow rate of 2 m 3 / h, countercurrent series exchange was carried out at a temperature of 97°C. When the material Ca at the top of the first exchange column 2+ When the exchange degree is 97%, the exchange intermediate is obtained by washing with deionized water at room temperature.
[0062] (5) The exchange intermediate was placed in an oven and dried at 120° C. for 1 h, and then an in-situ degassing / dehydration treatment was performed using a degassing activation device equipped on a Mack ASAP 3020 adsorption instrument. The dried exchange intermediate was treated at a temperature of 350° C. for 6 h, and the heating rate was set to 10° C. / min. The activated sample was naturally cooled to room temperature in a dryer to obtain the VPSA oxygen-generating molecular sieve, which had a silicon-aluminum ratio (SiO2 / Al2O3) of 2.04, a static nitrogen adsorption capacity (25° C., 760 mmHg) of 1.47 mmol / g, a nitrogen-oxygen separation coefficient (25° C., 760 mmHg) of 4.31, and a type A impurity crystal content of 0.5%.
[0063] Example 2
[0064] The VPSA oxygen-generating molecular sieve was prepared according to the method in Example 1, except that:
[0065] In step (3), the silicon-containing alkaline aqueous solution has a NaOH content of 2.4 mol / L and a SiO2 content of 9.4 g / L;
[0066] In step (4), the fresh calcium ion aqueous solution Ca 2+ The content is 1.6 mol / L, and the exchange temperature is 94°C;
[0067] The rest is the same as Example 1.
[0068] The prepared VPSA oxygen-generating molecular sieve has a silicon-aluminum ratio (SiO2 / Al2O3) of 2.05, a static nitrogen adsorption capacity (25°C, 760 mmHg) of 1.48 mmol / g, a nitrogen-oxygen separation coefficient (25°C, 760 mmHg) of 4.29, and a type A impurity crystal content of 0.7%.
[0069] Example 3
[0070] The VPSA oxygen-generating molecular sieve was prepared according to the method in Example 1, except that:
[0071] In step (3), the silicon-containing alkaline aqueous solution has a KOH content of 2.3 mol / L and a SiO2 content of 9.8 g / L, and is first crystallized at 62° C. in a countercurrent circulation for 2 h, and then crystallized at 92° C. in a countercurrent circulation for 4 h;
[0072] In step (4), the fresh calcium ion aqueous solution Ca 2+ The content is 2.3 mol / L, and the exchange temperature is 98°C;
[0073] The rest is the same as Example 1.
[0074] The prepared VPSA oxygen-generating molecular sieve has a silicon-aluminum ratio (SiO2 / Al2O3) of 2.01, a static nitrogen adsorption capacity (25°C, 760 mmHg) of 1.51 mmol / g, a nitrogen-oxygen separation coefficient (25°C, 760 mmHg) of 4.30, and a type A impurity crystal content of 0.6%.
[0075] Comparative Example 1
[0076] Chinese invention patent publication number CN113371730A discloses a method for preparing a modified calcium low-silicon zeolite molecular sieve. The prepared modified calcium low-silicon zeolite molecular sieve has a nitrogen adsorption capacity of 20.0 to 32.0 mL / g, i.e., 0.8928 mmol / g to 1.428 mmol / g, at 25°C and 0.1 MPa (absolute pressure).
[0077] Comparative Example 2
[0078] A primary calcined intermediate was prepared according to the method of steps (1) and (2) in Example 1; the primary calcined intermediate did not go through step (3) in Example 1, but directly went through steps (4) and (5) in Example 1. A VPSA oxygen-generating molecular sieve was prepared.
[0079] Comparative Example 3
[0080] The difference from Example 1 is that the number of drying and crushing in step (1) is one time, that is, one-time crushing powder is used, and the rest is the same as Example 1.
[0081] Comparative Example 4
[0082] The difference from Example 1 is:
[0083] In step (1), the molding liquid is deionized water;
[0084] In step (3), the silicon-containing alkaline aqueous solution has a NaOH content of 2.7 mol / L and a SiO2 content of 0 g / L;
[0085] The rest is the same as Example 1.
[0086] The prepared VPSA oxygen-generating molecular sieve has a silicon-aluminum ratio (SiO2 / Al2O3) of 2.01, a nitrogen adsorption capacity (25°C, 760 mmHg) of 1.36 mol / g, a nitrogen-oxygen separation coefficient (25°C, 760 mmHg) of 4.12, and a type A impurity crystal content of 2.4%.
[0087] The performance tests of the VPSA oxygen-generating molecular sieves prepared in the examples and comparative examples are as follows:
[0088] (1) Using an intelligent particle strength tester to analyze the crushing resistance of the molecular sieves prepared in the embodiment and the comparative example;
[0089] (2) Using an X-ray diffractometer to analyze the content of type A impurity crystals on the molecular sieves prepared in the examples and comparative examples;
[0090] (3) The static nitrogen adsorption capacity (25°C, 760 mmHg) and nitrogen-oxygen separation coefficient (25°C, 760 mmHg) of the molecular sieves prepared in the examples and comparative examples were analyzed using a micrometer adsorption instrument;
[0091] (4) The nitrogen adsorption rate (25°C, 760 mmHg) of the molecular sieves prepared in the examples and comparative examples was analyzed using a dynamic gravimetric vapor isobaric adsorption-desorption rate instrument.
[0092] The above test results are shown in Table 1.
[0093] Table 1 Main index determination results of molecular sieves prepared in Examples and Comparative Examples
[0094]
[0095]
[0096] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a VPSA oxygen-generating molecular sieve, characterized in that: The following steps are involved: The X-type molecular sieve raw powder, a binder, an organic pore-forming agent and a molding liquid are mixed and molded to obtain a molecular sieve intermediate; the X-type molecular sieve raw powder is a sodium-based or sodium-potassium-based X-type molecular sieve raw powder, D 50 The particle size is 0.1-1.0 μm, the silicon-aluminum ratio is 1.9-2.3, and the silicon-aluminum ratio is calculated as the molar ratio of SiO2 to Al2O3; the binder includes kaolin and / or kaolin; the molding liquid is a silicon source solution; The molecular sieve intermediate is subjected to a first drying and a first calcination in sequence to obtain a primary calcination intermediate; Using a silicon-containing alkaline aqueous solution to perform countercurrent circulation crystallization on the primary calcined intermediate to obtain a fully crystalline intermediate; The countercurrent cycle crystallization includes an aging stage and a crystallization stage in sequence; exchanging calcium ions on the fully crystalline intermediate to obtain an exchange intermediate; The exchange intermediate is sequentially subjected to a second drying and a second calcination to obtain the VPSA oxygen-producing molecular sieve.
2. The preparation method according to claim 1, characterized in that: The silicon-to-aluminum ratio of the binder is 1.75-2.3, and the silicon-to-aluminum ratio is calculated as the molar ratio of SiO2 to Al2O3.
3. The preparation method according to claim 1, characterized in that: The organic pore-forming agent includes one or more of corn starch, wheat starch and bran.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The masses of the binder and the organic pore former are 5-10% and 0.5%-4% of the total mass of the X-type molecular sieve raw powder and the binder respectively, and the masses of the binder and the X-type molecular sieve raw powder are calculated on a dry basis.
5. The preparation method according to claim 1, characterized in that: The silicon source in the silicon source solution includes one or more of white carbon black, silica gel powder, sodium silicate and silica sol. The content of the silicon source in the silicon source solution is 2.0-6.0 g / L, and the content of the silicon source is calculated as SiO2.
6. The preparation method according to claim 1, characterized in that: The molding method is: The mixture of X-type molecular sieve raw powder, binder and organic pore-forming agent is sequentially mixed with molding liquid, first molded, dried and crushed to obtain crushed powder; the operations of mixing with molding liquid, first molded, dried and crushed are repeated, and the number of repetitions is ≥1 times; The crushed powder is mixed with a molding liquid for a second molding to obtain a molecular sieve intermediate.
7. The preparation method according to claim 1, characterized in that: The silicon content in the silicon-containing alkaline aqueous solution is 5 to 19 g / L, and the silicon content is calculated as SiO2; the OH in the silicon-containing alkaline aqueous solution is 1.5 to 2.5 g / L. - The content is 2.26-2.90 mol / L; the solid-liquid ratio of the primary calcined intermediate to the silicon-containing alkaline aqueous solution is 1 kg:2.2-3.0 L.
8. The preparation method according to claim 1 or 7, characterized in that: The temperature of the aging stage is 50-70°C, the time is 1-4 hours, and the countercurrent circulation flow rate of the silicon-containing alkaline aqueous solution is 1-4 m 3 / h; the temperature of the crystallization stage is 80-100°C, the time is 3.5-7h, and the countercurrent circulation flow rate of the silicon-containing alkaline aqueous solution is 1-4m 3 / h.
9. The preparation method according to claim 1, characterized in that: The temperature of the first drying is 80-200°C, and the insulation time is 0.5-4h; the temperature of the first roasting is 620-750°C, and the insulation time is 0.5-4h; the temperature of the second drying is 50-120°C, and the insulation time is 1-2h; the temperature of the second roasting is 350-425°C, and the insulation time is 3-8h.
10. The VPSA oxygen-producing molecular sieve prepared by the preparation method according to any one of claims 1 to 9, wherein the VPSA oxygen-producing molecular sieve has an X-type molecular sieve crystal structure, does not contain a binder, and has a silicon-aluminum ratio of 1.9 to 2.3, wherein the silicon-aluminum ratio is calculated as the molar ratio of SiO2 to Al2O3.
Citation Information
Patent Citations
Modified calcium low-silicon zeolite molecular sieve and preparation method thereof
CN113371730A